Análise do desempenho de estações convencionas de tratamento de água de distintos portes, operando em escala real - Gabriela Rodrigues Barroso (2020)
Water treatment plants (WTPs) are extremely important for the potabilization of water to be distributed to the population, minimizing the public health risks from the consumption of water with improper quality. In Brazil, most WTPs use conventional treatment. In this context, the present work aims to analyze the performance of conventional water treatment plants of different sizes operating in Brazil, in real scale, using statistical techniques. In this research, 21 plants were analyzed considering daily monitoring data, from January 2012 to December 2016. The water quality parameters selected for analysis were: turbidity and apparent color of raw, decanted and treated water; pH of raw water and treated water; chlorine and fluorine concentrations of treated water. In addition, information of flow and coagulant dosage from the WTPs was obtained. Nonparametric tests and reliability analysis were employed to evaluate the performance of the WTPs individually and by size. In general, the results indicated better performance of large plants in terms of treated water quality compared to small and medium plants, which may be related to better operating conditions. The percentage of compliance of the Brazilian potability standard for apparent color, pH, chlorine and fluorine was 100% for most of the analyzed WTPs, while the turbidity standard was successfully met in only 10 plants. The reliability analysis also indicated better performance of large WTPs, since maintaining the same operating conditions, these WTPs can reach higher percentages of compliance to turbidity standards than the other sizes WTPs. However, most plants, independent of size, showed difficulty in meeting more restrictive potability standards already adopted in other countries, which indicates the importance of continuous and thorough evaluation of monitoring data as well as the design and operation conditions of the plants aiming to propose improvements.